Powder reuse and variability in laser powder bed fusion additive manufacturing of Ti6Al4V: A round robin study - A. Montelione; R. Schur; R. Schleusener; M. Ramulu; D. Arola (Journal of Materials Research and Technology)
A powder reuse study was performed within a round robin investigation involving six different EOS M290 Laser Powder Bed Fusion (L-PBF) machines, each associated with a different manufacturer and site. An identical sequence of six builds was performed on each machine using the same lot of plasma atomized grade 5 Ti–6Al–4V powder. Samples of powder were taken prior to each build and analyzed to characterize the particle size distribution, morphology, bulk chemistry, and flowability. The mean particle size of the powder as well as its flowability increased slightly with reuse at all sites, whereas the powder chemistry did not change appreciably over the six builds conducted. While no trend was observed in the overall powder chemistry between builds, there were significant differences in powder chemistry between participants in the later builds. This finding suggests that powder degradation is driven by location specific details such as environmental or procedural factors. Furthermore, the mean particle size was found to vary across the build area, whereas the particle morphology did not change noticeably between builds or locations. Quasi-static mechanical properties of the metal produced with the reused powder correlated with the carbon and aluminum content, but not with number of reuse cycles. The tensile properties exhibited higher variation between participants than they did between builds. Overall, these results highlight the potential variability in quality of reused powder and differences in its rate of “aging” in L-PBF across manufacturers, even when the machine model and starting powder lot is highly controlled.